2007
DOI: 10.1111/j.1471-4159.2007.05113.x
|View full text |Cite
|
Sign up to set email alerts
|

CSF proteomic analysis reveals persistent iron deficiency‐induced alterations in non‐human primate infants

Abstract: Iron deficiency (ID) anemia during infancy results in long‐term neurological consequences, yet the mediating mechanisms remain unclear. Infant monkeys often become naturally anemic during the first 6 months of life, presenting an opportunity to determine the effect of developmental iron deficiency. After weaning, animals were chosen randomly for supplementation with oral iron or, fed a standard commercial chow diet. The control group was never iron deficient. ID anemia was corrected by 12 months in both groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 44 publications
2
27
0
Order By: Relevance
“…In the ID individual, there may be a further prioritizing of iron to bone marrow, liver, spleen, and red blood cells, which may be placing the brain needs for iron in jeopardy. Our finding of a delayed but sustained effect on the CNS also concurs with a prior proteomic analysis of CSF from a different group of ID monkeys, which indicated that their iron regulatory proteins were increased and the intrathecal proteome disturbed for at least 4 months after the period of anemia had ended (Geguchadze, Coe, Lubach, Clardy, Beard, & Connor, 2008). …”
Section: Discussionsupporting
confidence: 90%
“…In the ID individual, there may be a further prioritizing of iron to bone marrow, liver, spleen, and red blood cells, which may be placing the brain needs for iron in jeopardy. Our finding of a delayed but sustained effect on the CNS also concurs with a prior proteomic analysis of CSF from a different group of ID monkeys, which indicated that their iron regulatory proteins were increased and the intrathecal proteome disturbed for at least 4 months after the period of anemia had ended (Geguchadze, Coe, Lubach, Clardy, Beard, & Connor, 2008). …”
Section: Discussionsupporting
confidence: 90%
“…One protein identified by our iTRAQ study that was also altered in our previous study [19] was prostaglandin H2-D-isomerase, which is also referred to as prostaglandin D2 synthase (PGDS), and functions to catalyze the conversion of prostaglandin H2 to PGD2. PGDS is produced in the leptomeninges and choroid plexus, and the enzymatic product PGD2 is a neuromodulator as well as a trophic factor in the CNS.…”
Section: Discussionmentioning
confidence: 78%
“…The iTRAQ methodology was chosen because it not only identifies proteins of interest, but also permits accurate quantification, allowing for key comparisons in a systematic manner. A previous study of IDA in infant monkeys using 2D analyses [19] revealed that a distinct CSF protein profile persisted for over 4 months after the period of anemia, and it was still evident in infants that received 2 months of ferrous sulfate treatment. The current results confirm and extend those findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This expression pattern for Tf and ferritin when seen in the serum is considered an indicator of systemic iron deficiency. Elevated CSF Tf levels also were observed in a developmental non-human primate model of iron deficiency, despite supplementation with iron and resolution of hematological iron deficiency [27]. The persistence of elevated Tf in CSF despite repletion of systemic iron brings up the possibility that a set point for iron status in the brain was altered during development that may render the brain sensitive to iron challenges into adulthood.…”
Section: Introductionmentioning
confidence: 99%